2004
DOI: 10.1111/j.0013-9580.2004.458009.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistics on Deliveries of Mothers with Epilepsy at Yokohama City University Hospital

Abstract: Summary:Purpose: To survey and summarize the treatment of pregnant women with epilepsy and to obtain data for the improvement of daily treatment regimens.Methods: We reviewed medical records of 36 deliveries of 25 mothers with epilepsy at Yokohama City University Hospital from September 1991 to December 2000 and statistically compared the differences in drug-taking profiles, complications during pregnancy, types of delivery, and complications at delivery between the epilepsy group and a control group (656 tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
5
9
0
1
Order By: Relevance
“…The induction rate in women with epilepsy was increased, mainly in those using AEDs. This is in accordance with some previous studies, 6,15,23 but contrary to the findings in others, where no difference was seen 18,43 . According to guidelines, 1,44 epilepsy is not an indication for induction in uncomplicated pregnancies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The induction rate in women with epilepsy was increased, mainly in those using AEDs. This is in accordance with some previous studies, 6,15,23 but contrary to the findings in others, where no difference was seen 18,43 . According to guidelines, 1,44 epilepsy is not an indication for induction in uncomplicated pregnancies.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors have demonstrated increased risks of gestational hypertension, 15,16 pre-eclampsia 4,16,17 and bleeding in pregnancy 4 compared with the general population, whereas others could not demonstrate such differences. 5,6,18 It is unclear whether or not any increased risk of complications occurs because of epilepsy per se, the use of AEDs 19 or other factors affecting women with epilepsy. If the effect of AEDs is important, the change to newer AEDs may lead to changes in these risks.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Similarly, in our study, seizure frequency remained the same in 70.1% of the cases.…”
Section: Discussionsupporting
confidence: 81%
“…As a doctor or patient, one should start with a preconception dialogue with a focus on the importance of a planned pregnancy with optimizing AED use, folate supplementation, the teratogenicity of AEDs versus the risks of seizures, and the risk of obstetric complications [53]. Two studies on women treated with the old-generation AEDs have reported increased risks of bleeding in pregnancy, preeclampsia and preterm birth [54,55], but this has not been replicated in other studies [3][4][5][56][57][58]. It has been discussed whether differences in AED use or the epilepsy type cohort are responsible for these differences [59].…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…According to guidelines in England and Norway, induction of labor should be evaluated on an individual basis [69,101]. Deliveries with forceps and vacuum are not increased in women with epilepsy [3][4][5]70]. This may be due to the high rates of CD, but may also reflect few complications during labor.…”
Section: Delivery Outcomementioning
confidence: 99%